MR imaging: possibility of tissue characterization of brain tumors using T1 and T2 values. - Komiyama, M; Yagura, H; Baba, M; Yasui, T; Hakuba, A; Nishimura, S; Inoue, Y (American Journal of Neuroradiology, 1987)
To evaluate the usefulness of T1 and T2 values for tissue characterization of brain tumors, 37 histologically confirmed brain tumors were examined with a 0.5-T superconductive MR system. With spin-echo and inversion-recovery imaging sequences, computed T1 and T2 images were reconstructed, and T1 and T2 values of the tumors were calculated. Relaxation rates (1/T1 and 1/T2), T1/T2 ratios, and malignancy indexes, which were originally designed for gastrointestinal tumors, were also calculated. Values of all these parameters were so wide-ranged that it was impossible to characterize the tumor tissue types.